Influence of Temperature on Initiation Mechanism of Partial Discharge at the Interface Defects of Cable Accessories - Weiwei LI; Ke ZHU; Yuanshi DENG; Zikang WANG; Yonglu HUANG; Kai ZHOU (Zhongguo dianli)
Temperature has an important influence on the partial discharge (PD) development, but the effect of temperature on the PD initiation mechanism is still not fully understood. Thus, this paper investigated the influence of temperature on the PD initiation mechanism at the interface defects of cable accessories. First, the interface unit and defects of cable accessories were designed and simulated, and the PD features of air-gap defects under different temperature were measured. Then, an electrothermal aging platform for cables with semi-conductive-layer protrusion defects was constructed, simulating the influence of cooling and heating loads on the operating temperature of cables through the on-off current. Afterward, the partial discharge inception voltage (PDIV) and the phase resolved partial discharge (PRPD) spectrum of samples were analyzed comparatively. Obtained results showed that, as the test temperature applied on the unit increased, PDIV would decrease from 8.3 kV to 6.9 kV accordingly, and the PRPD spectrum presented obvious internal discharge characteristics. Meanwhile, tests on the actual defects of the cable accessory showed that when the temperature rose quickly, the temporary PD excitation occurred and the number and amplitude of PD increased significantly. When the temperature was stabilized, however, the increment slowed down. The phenomenon can be interpreted through the space charge distribution of the interface due to temperature changes and the “breathing effect” caused by the thermal expansion and contraction of the interface material. The research reveals that PD signals in the interface defect are easier to be detected when cable accessories are operating under high temperature gradient, which may provide theoretical references for the unreliability of traditional PD detection.